MENJELAJAHI SPESIES BURUNG DI PULAU BREUEH, KECAMATAN PULO ACEH, PROVINSI ACEH - Yuri Gagarin; Tarmizi, Heri; Muarrif, Samsul; Muhajir, Muhajir; Abdullah, Abdullah (KENANGA : Journal of Biological Sciences and Applied Biology, 2025)
Pulau Breueh, located in Pulo Aceh District, Aceh Besar Regency, Aceh Province, Indonesia, is renowned for its rich avifaunal diversity. However, comprehensive data on bird species distribution and abundance on the island remain limited, highlighting the need for detailed studies to support conservation efforts. This study aimed to document and analyze the bird species present on Pulau Breueh, focusing on their distribution across various habitats. Field observations were conducted in July 2024 using two methods: the transect method, covering a 20 km route across coastal and inland areas, and the point count method, with observations at strategic locations. A total of 34 bird species from 19 families were identified, including coastal species such as the Pacific Reef Egret (Egretta sacra) and forest-dwelling birds like the Crested Serpent Eagle (Spilornis cheela). The findings underscore the ecological significance of Pulau Breueh as a habitat for diverse avian communities and emphasize the importance of conservation measures to mitigate threats such as habitat alteration and hunting. Recommendations include habitat protection, community education, and continuous monitoring to preserve this biodiversity hotspot. Keywords: bird; Pulau Breueh; biodiversity; conservation